Breast implant illness: scientific evidence of its existence. (2nd January 2022) - Cohen Tervaert, JW; Mohazab, N; Redmond, D; van Eeden, C; Osman, M.
ABSTRACT: Introduction: More than one million breast augmentation procedures using silicone breast implants (SBI) have been performed worldwide. Adverse events of SBI include local complications such as pain, swelling, redness, infections, capsular contracture, implant rupture, and gel-bleed. Furthermore, patients experience systemic symptoms such as chronic fatigue, arthralgias, myalgias, pyrexia, sicca, and cognitive dysfunction. These symptoms received different names such as autoimmune/autoinflammatory syndrome induced by adjuvants (ASIA) due to silicone incompatibility syndrome and breast implant illness (BII). Because of chronic immune activation, BII/ASIA, allergies, autoimmune diseases, immune deficiencies, and finally lymphomas may develop in SBI patients. Areas covered: Causality for SBI-related BII/ASIA is reviewed. To address the role of silicone implants in promoting causality, we utilized the Bradford Hill criteria, with results highlighted in this article. Expert opinion: We conclude that there is a causal association between SBIs and BII/ASIA. Using data derived from patients with BII/ASIA and from other medically implanted devices, there appears to be clear pathogenic relationship between SBI and BII/ASIA. Breast implants cause characteristic systemic reactions in certain women, leading to symptoms of sufficient severity to warrant device removal. The morbidity suffered is variable. SBI removal resolves the symptoms in most women, and removal is the most effective treatment.